Infinity and extensive magnitude.On the transcendental notion of infinity as the foundation of the procedure of synthesis of extensive magnitudes - López López, Alberto (Con-Textos Kantianos. International Journal of Philosophy, 2025)
The aim of the present paper is to clarify how the procedure of synthesis of the extensive magnitudes is based on the infinite given magnitude adopting, for this purpose, an approach based on a stratified model of constitution. For this purpose, the paper develops the following structure. First, we start from a problematization of the procedure of synthesis of extensive magnitudes and show how it requires the introduction of the notion of infinity. Secondly, we carry out an analysis of space and time as infinite given magnitudes and of the transcendental concept of infinity in order to show in what sense such infinity grounds the synthesis of the extensive magnitude. Thirdly, we introduce the distinction between potential infinity and actual infinity in order to clarify this foundation. Finally, in the conclusions we describe the levels of constitution of space and time (and magnitudes) on the basis of the preceding argumentation.